Development of handicraft web based system using agile approach / Roziah Sulaiman - Sulaiman, Roziah (2012)
Handicraft product is an artistic product that makes a village significant due to its uniqueness. In Kampung Tengah, producing handicraft product is one of the source incomes of the community. However, the product information is known by small group of people. This is because they do not have web based system to disseminate their handicraft product information. This project aim to provide handicraft web based system to Kampung Tengah which provide the information of their indigenous product. This project has used agile approach with three iterations for the development of this web base system. The first iteration began with gathering the initial user requirement. Then, the requirement was analyzed and a system was designed and developed accordingly. The system then went through the first process of user testing. Feedback from the user in this iteration was analyzed, and used to designed and developed an improved system. This process was repeated three times, and system was improved in each iteration. After three iterations, the final prototype was concluded. The development of handicraft web based system will help Kampung Tengah to disseminate their indigenous product to the public. Additionally, it will help to increase the number of potential customer for their handicraft product as well as attract more tourist to visit their village.